PILOTING A NEW APPROACH TO IDENTIFYING, ASSESSING AND SUPPORTING CARERS OF PEOPLE WITH PALLIATIVE CARE NEEDS IN PRIMARY CARE. Issue 1 (1st March 2015) - Carduff, E; Highet, G; Finucane, A; Kendall, M; Jarvis, A; Harrison, N; Greenacre, J; Murray, SA
Abstract : Introduction: UK general practices are incentivised to "have a protocol for the identification of carers and a mechanism for referral for social services assessment". This is rarely done systematically and very few carers of patients with palliative care needs are identified. Thus they fail to receive support. Aim(s) and method(s): To model and pilot a systematic approach to identifying, assessing and supporting carers of people with palliative care needs in primary care. Four general practices which varied in size were recruited to pilot a theoretically modelled intervention for 12 months. Each practice nominated a carer liaison to lead on carer identification and support. Results: The practices varied in size from 5840 to 10832 patients. 83 carers were identified across the 4 practices via registers; illness (12), palliative care (12), carer (11); advanced care plans (12) or opportunistically (28) at GP appointments or at home. 7 carers self-identified. There were 55 female and 28 male carers. Overall, 81 carers received the intervention and 25 returned the Carer Support Needs Assessment Tool (CSNAT). On average carers each identified 4/14 areas of need. 11 carers received a follow up call from the practice to discuss support. 12 carers were also referred for support. Conclusion(s): The findings suggest that the new approach to identifying and supporting carers was feasible, but had to be embraced by the whole practice. Carers did not tend to self-identify, nor ask for help. Practices need to be motivated and equipped with information about local carer support and take measures to empower carers to self-identify.